Effect of different bonding protocols on degree of monomer conversion and bond strength between orthodontic brackets and enamel - Lorena Marques Ferreira de SENA; Helga Adachi Medeiros BARBOSA; Sergei Godeiro Fernandes Rabelo CALDAS; Mutlu OZCAN; Rodrigo Othávio de Assunção e SOUZA (Sociedade Brasileira de Pesquisa Odontológica, 2018)
Abstract The objective of the present study was to evaluate the effect of different surface treatments and polymerization protocols on the bond strength of brackets to enamel, and the degree of conversion of the bonding agents. 120 bovine crowns were embedded in acrylic resin blocks and sanded. Next, the blocks were randomly assigned into 12 groups. Metal brackets were bonded to enamel according to the "surface treatment" factor (A: Phosphoric Acid; ATxt: Phosphoric Acid + Transbond XT Primer®; Tse: Transbond Plus Self Etching Primer®; and SBU: Scotchbond Universal®) and "polymerization" factor (R20: Radii-Cal®/20 seconds; V20: Valo Cordless®/20 seconds; and V3: Valo Cordless®/3 seconds). All samples were stored for 6 months (water, 37ºC) and then subjected to a shear bond strength test (SBS). Bond failures were classified according to the Adhesive Remnant Index (ARI) and analyzed with the Kruskal-Wallis and Mann-Whitney tests (5%). Using the same factors, 120 resin discs were made to assess the degree of conversion (DC) of the monomer. Data from the SBS (MPa) and DC (%) were analyzed by analysis of variance (2 factors) and Tukey's test (5%). For the SBS, the factors "polymerization" (R20 = 8.1B; V20 = 13.2A; V3 = 5.2C, p = 0.0001) and "surface treatment" (A = 3.1C; ATxt = 13.6A; Tse = 12.3A; SBU = 6.3B, p = 0.0001) were statistically significant among groups. The highest adhesion value were found for the ATxt/V20 group (22.2A) and the lowest value for the A/R20 group (1.2E). Regarding ARI, score 2 was the most prevalent in groups A, ATxt, V20 and V3, while score 4 was the most prevalent in the Tse, SBU and R20 groups, with no significant difference between them (p = 1.0). Regarding DC, the factors "polymerization" (R20 = 66.6A; V20 = 58.4B; V3 = 45.1C, p = 0.0001) and "surface treatment" (A = 52B, ATxt = 59.7A, Tse = 51.4B, SBU = 63.8A, p = 0.0001) were statistically significant. Tse was more sensitive to the variations in polymerization protocols than the other surface treatments. Treatment A did not present suitable bond strength or degree of conversion.